Huntington's disease with severe neck infection. (19th May 2017) - Hino, Shunsuke; Kaneko, Takahiro; Horie, Norio; Shimoyama, Tetsuo
Abstract : Objective: To present a case of Huntington's disease (HD) with severe neck infection. Background: Huntington's disease (HD) is a progressive neurodegenerative genetic disorder and is often accompanied by dysphagia. Materials and methods: The patient was a 64‐year‐old man with HD. The severe neck infection was considered as one of the symptoms of HD. Conclusion: Clinicians should remember that patients with HD are apt to delay dental consultation, resulting in serious oral infections.